Cold micro metal forming : research report of the Collaborative Research Center "Micro Cold Forming" (SFB 747), Bremen, Germany : final report of the DFG Collaborative Research Center 747 /: research report of the Collaborative Research Center "Micro Cold Forming" (SFB 747), Bremen, Germany : final report of the DFG Collaborative Research Center 747. (2020) - Unknown
No abstract available